The effects of an enrichment training program for youth football attackers - Coutinho, Diogo (2019)
This work was supported by the Portuguese Foundation for Science and Technology (FCT, Portugal) through a Doctoral grant endorsed to the first author (SFRH/BD/ 105081/2014) under the Human Potential Operating Program (POPH). Research Project NanoSTIMA: Macro-to-Nano Human Sensing: Toward Integrated Multimodal Health Monitoring and Analytics, NORTE-01-0145-FEDER-000016, Fundo Europeu de Desenvolvimento Regional (FEDER) - NORTE 2020. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.